2015
DOI: 10.1038/srep09667
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport in two-dimensional high dielectric constant nanosystems

Abstract: There has been remarkable recent progress in engineering high-dielectric constant two dimensional (2D) materials, which are being actively pursued for applications in nanoelectronics in capacitor and memory devices, energy storage, and high-frequency modulation in communication devices. Yet many of the unique properties of these systems are poorly understood and remain unexplored. Here we report a numerical study of hopping conductivity of the lateral network of capacitors, which models two-dimensional insulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…We consider a network model that consists on N sites at random on a square sample of size L × L = N and capacitors in the links joining nearest neighbor sites. Each site corresponds to a metallic grain (or set of metallic grains as explained bellow) and each capacitor to the capacitance between nearest neighbor grains 19 . A scheme of the network model is shown in Fig.…”
Section: Fig 4 Top and Side Views Of The Scheme Of The Capacitors Nmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider a network model that consists on N sites at random on a square sample of size L × L = N and capacitors in the links joining nearest neighbor sites. Each site corresponds to a metallic grain (or set of metallic grains as explained bellow) and each capacitor to the capacitance between nearest neighbor grains 19 . A scheme of the network model is shown in Fig.…”
Section: Fig 4 Top and Side Views Of The Scheme Of The Capacitors Nmentioning
confidence: 99%
“…It is convenient to define the following charge vector of dimension N + 2 (see Ref. 19 for details of the model)…”
Section: Fig 4 Top and Side Views Of The Scheme Of The Capacitors Nmentioning
confidence: 99%
See 1 more Smart Citation
“…On the fundamental side the interest is motivated by the challenge of understanding the behavior of a 2D Coulomb glass, a highly frustrated strongly correlated system whose properties are governed by the intertwined effects of disorder and the long-range LI [26]. An impor-tant step has been done in our previous publication [27] where hopping conductivity of a 2D Coulomb glass was investigated via a first-principle numerical study. We demonstrated that hopping transport is controlled by the characteristic energy that scales as E a ∝ lnL with L = min{L, Λ}.…”
mentioning
confidence: 99%
“…. Recent investigations by Ortuño et al on the electronic transport in 2D layers with high dielectric constants, reveal the existence of a nonlocal conductivity, σ, with a dependence on distance L as σ = σ 0 exp (γ/ L ). In any case, we note that whatever the model, the transport current is expected to decay rapidly with the radius of the spot, until it becomes irrelevant, as concluded previously from the analysis of Q ( t ) in Figure .…”
Section: Discussionmentioning
confidence: 99%